Respiração edáfica, atributos agronômicos e fisiológicos de plantas de pimentão sob adubação biológica - Leal, Ygor Henrique (2019)
Biological fertilization improves the chemical, physical and biological characteristics of the soil, presenting the potential to replace synthetic fertilizers, promoting the greater productive and vegetative performance of the crops. The objective was to evaluate the soil respiration and the agronomic and physiological attributes of pepper plants (Capsicum annuum) under doses and times of application of biological fertilizers. Two experiments were carried out with applications of biological fertilizers prepared from manure and enriched organic compound, one using bovine manure (ABB) in its composition and the other, sheep manure (ABO). The experiment was carried out in a randomized complete block design, in a 4 x 3 + 1 factorial scheme, with three replications, for four doses of biological fertilizers (100, 200, 300 and 400 dm³ ha-1), three application times (0, 30 and 60 DAT) and an absolute control. Variables involved in edaphic respiration were evaluated in the day and night shifts (soil surface temperature, Tsup, and 10 cm depth, T10, soil moisture, U and edaphic respiration, RE), on plant growth , Number of leaves, NF, length of leaf, CF, leaf width, LF and leaf area, AF), morphological and yield attributes of sweet pepper (number commercial fruit, NFC, and non-commercial, NFNC; fruit diameter, DF; length of fruits, CF; resistance of the fruit peel, RCF; number of flower buds, NBF; total weight of fruits, PTF; mean weight of fruits, PMF; and productivity, P) and gaseous and chlorophyll exchange variables (liquid photosynthesis, A, stomatal conductance, gs, internal CO2 concentration, Ci, instantaneous carboxylation efficiency, EiC - A / Ci, transpiration rate, and intrinsic efficiency of use of water, EIUA - A / gs; water use efficiency, USA - A / E; the relative index of chlorophyll a, b and total; and chlorophyll a / b ratio). The ABO provided higher Tsup, T10 and RE scores in the two shifts evaluated, except for Tsup and T10 at night. At the time of day, only the treatments in which ABO 400 and 300 dm³ ha-1 were applied, in the seasons of 0 and 30 DAT, respectively. ABB provides longer leaf length, leaf width and leaf area in the sweet pepper. Biological fertilizers caused positive effects on PTF, NFC, PMF and P of the sweet pepper. The dose of 300 dm³ ha-1 at 30 DAT promotes a significant increase in the diameter of sweet peppers. A gs, A and E, had an effect on the 60 DAT with the ABO application and the Ci at 30 DAT with ABB. The ABO 400 dm³ ha-1 dose provided higher gs results, and the ABB 200 and 300 dm³ ha-1 doses promoted higher Ci. The EiC showed difference with the application of ABO at 60 DAT. The total chlorophyll index was higher with the application of ABB at the time of 0 DAT.